The Gilets Jaunes: Offline and Online - Pierre C. Boyer; Thomas Delemotte; Germain Gauthier; Vincent Rollet; Benoît Schmutz (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the Gilets jaunes movement, which blocked most of France off in November 2018. We first analyze the complementarity/substitutability between the different forms of mobilization and find that blockades were planned online and later reinforced online activism. Second, we do textual analysis and show that online discussions evolved from local concerns to widespread critique. Finally, while the Gilets jaunes refused to designate candidates for the subsequent European elections, we ask whether the movement had electoral consequences nonetheless. We show that blockades boosted the performance of the government's party in its bastions, except when they nurtured further online dissent.
Keywords: F15; J40; J60; J80; C83; 330; gilets jaunes; yellow vests; protests; social media; spatial inequalities